Central Blood Pressure and Augmentation Index in Older Adults With Intellectual Disabilities - Mc Carron, Mary; O'Brien, Frances; Burke, Eilish; Mc Callion, Philip; Ryan, Cristn (My University, 2025)
Background: Older adults with intellectual disabilities are at a higher cardiovascular risk than their peers in the general population. Investigating central blood pressure and augmentation index is necessary to better understand the risk of cardiovascular disease, to better identify those individuals at risk and to potentially change pharmacological treatment regimens. We therefore aim to investigate central blood pressure and augmentation index in two large cohorts (total N = 237) of older adults with intellectual disabilities, across different age ranges and sexes. Additionally, we will explore the cross-sectional relationships of central blood pressure and augmentation index with other cardiovascular risk factors and the presence of cardiovascular disease across a broad age range. Method: Collected data of two cohorts of older adults with intellectual disabilities were included: n = 121 individuals with intellectual disabilities of ≥ 60 years from the Healthy Ageing and Intellectual Disabilities (HA-ID) study, and n = 115 individuals with intellectual disabilities ≥ 40 years from The Intellectual Disability Supplement to the Irish Longitudinal Study on Ageing (IDS-TILDA) study. The Mobil- O- Graph was used to measure central blood pressure and augmentation index. The distribution of haemodynamic measures across different sex and age groups was reported, and bivariate correlations were calculated to explore associations between haemodynamic measures, cardiovascular risk factors and history of CVD. Results: Mean brachial pressures for the HA-ID cohort (mean age 71 ± 6 years) was 133/81 mmHg. The slightly younger IDS-TILDA cohort (mean age 60 ± 9 years) had a median brachial blood pressure of 127/81. Mean central SBP (cSBP) in the older HA-ID cohort was 122 mmHg versus 120 mmHg in the younger IDS-TILDA cohort, with a central DBP (cDBP) of 82 mmHg 2 of 14 Journal of Intellectual Disability Research, 2025 in both cohorts, and a central pulse pressure (cPP, cSBP- cDBP) of 40 mmHg for the HA-ID cohort and 38 mmHg for the IDS-TILDA cohort. Conclusions: Females with intellectual disabilities had higher central blood pressures, augmentation pressure and augmentation index than males, and females showed an age-related increase in central blood pressures.
PUBLISHED
Keywords: intellectual disability; down syndrome; central blood pressure; cardiovascular risk; augmentation index; ageing